Platform work and social security in German law: An international law perspective - Eichenhofer, Eberhard (International social security review (English edition), 2021)
Platform work confronts traditional social security law in two dimensions. First, it makes the distinction between dependent and independent work uncertain and unclear, as the borderline between these blur. This is a profound challenge for social security law, because the criteria of dependent and independent work have to be precise. In the determination of work as dependent or independent, German law illustrates that a shift has taken place in determining employment status, moving from external and objective criteria to the contracting parties’ decision, which is to be executed under private law, but also respected under social security law. Second, platform work is heavily intertwined with digital communication, which has established a global environment for communication. Thereby, platform work can also facilitate international trade by making transnational work more accessible and efficient. Therefore, it seems necessary to examine the implications of platform work in international law. International law makes possible the choice of law, executed by the contracting parties. As a consequence, the protection of employees by social security law is related to the private law arrangements between the service provider and the service recipient. Gaps in social security protection of service providers are widespread. In many countries, awareness of the social protection deficits of platform workers has grown and responses to improve the social status of platform workers have come under scrutiny. Analysis reveals that there is a joint responsibility of the service provider and the service recipient to be bound to social security coverage under the same national legislation. Nevertheless, from an international law perspective, it is shown that reforms are confronted with restrictions under international law. Le travail des plateformes pose un problème au droit de la sécurité sociale traditionnel pour deux raisons. Premièrement, il rend la distinction entre travail salarié et travail indépendant floue et incertaine parce qu’il brouille la frontière entre ces deux statuts. Il s’agit là d’un défi de taille pour le droit de la sécurité sociale du fait que les critères qui permettent de qualifier une activité de salariée ou d’indépendante doivent être précis. À cet égard, le droit allemand montre qu’une évolution a eu lieu en ce sens que la détermination du statut professionnel repose, non plus sur des critères extérieurs et objectifs, mais sur la décision des parties contractantes, laquelle doit être exécutée en droit privé mais aussi respectée dans le cadre du droit de la sécurité sociale. Deuxièmement, le travail de plateforme est étroitement lié à la communication numérique, qui a créé un environnement de communication de dimension mondiale. Il peut donc aussi favoriser le commerce international parce qu’il facilite le travail transfrontalier et le rend plus efficient, d’où la nécessité d’étudier ses répercussions sous l’angle du droit international. Le droit international permet de choisir le droit dont relèvent les parties contractantes. Dès lors, la protection des travailleurs par le droit de la sécurité sociale dépend du contrat de droit privé conclu entre le prestataire et le bénéficiaire des services. Il existe très souvent des lacunes dans la protection sociale des prestataires de services, et beaucoup de pays prennent conscience de l’insuffisance de la couverture des travailleurs des plateformes et étudient des solutions pour y remédier. L’analyse montre que le prestataire et le bénéficiaire des services ont l’un et l’autre des obligations en matière de sécurité sociale en vertu de la même législation nationale. Néanmoins, les réformes sont limitées par des contraintes imposées par le droit international. El trabajo en las plataformas plantea un problema para la legislación tradicional en materia de seguridad social por dos razones. Primero, difumina la línea que distingue entre el trabajo por cuenta propia y el trabajo por cuenta ajena. Esto plantea un difícil desafío para la legislación en materia de seguridad social, puesto que los criterios para definir el trabajo por cuenta propia y el trabajo por cuenta ajena deben ser precisos. A este respecto, el derecho alemán pone de manifiesto que se ha producido un cambio en el sentido de que la determinación de la situación laboral ya no se basa en criterios externos y objetivos, sino en la decisión de las partes contratantes, la cual debe aplicarse en el marco del derecho privado, aunque también deberá respetar la legislación en materia de seguridad social. Segundo, el trabajo en plataformas está estrechamente vinculado a la comunicación digital, que ha creado un entorno de comunicación mundial. Así, el trabajo en las plataformas también puede facilitar el comercio internacional, haciendo que el trabajo transnacional sea más accesible y eficiente. Por lo tanto, parece necesario examinar las implicaciones del trabajo en las plataformas en la legislación internacional. Gracias a la legislación internacional se puede elegir la legislación a la que van a acogerse las partes contratantes. Como consecuencia, la protección de los empleados mediante la legislación de seguridad social está relacionada con los acuerdos de derecho privado concertados entre el proveedor de servicios y el destinatario de los servicios. Las deficiencias en la protección de la seguridad social de los proveedores de servicios se han generalizado. Muchos países cada vez son más conscientes de las deficiencias en la protección social de los trabajadores de plataformas y han empezado a analizarse las respuestas para mejorar la condición social de dichos trabajadores. El análisis revela que el proveedor de servicios y el destinatario de los servicios tienen una responsabilidad conjunta con respecto a la cobertura de seguridad social en el marco de la misma legislación nacional. Sin embargo, las reformas están limitadas por las restricciones impuestas por el derecho internacional. Plattformarbeit stellt die herkömmliche Gesetzgebung der sozialen Sicherheit vor zweierlei Herausforderungen. Erstens lassen sich lohnabhängige und selbstständige Beschäftigung nicht mehr genau voneinander trennen, da die Grenzen verschwimmen. Dies ist ein grundlegendes Thema für die Sozialversicherungsgesetzgebung, da die Unterscheidungskriterien zwischen lohnabhängiger und selbstständiger Arbeit genau festgelegt sein müssen. Hinsichtlich der Unterscheidung zwischen lohnabhängiger und selbstständiger Arbeit zeigt das deutsche Recht, dass bei der Bestimmung des Beschäftigungsstatus eine Verlagerung weg von externen und objektiven Kriterien hin zu einer Vereinbarung der Vertragsparteien stattgefunden hat, die nach Privatrecht umzusetzen ist, aber auch vom Recht der sozialen Sicherheit anerkannt wird. Zweitens ist Plattformarbeit stark an eine digitale Kommunikation gebunden, die den ganzen Globus umspannt. Plattformarbeit kann daher auch den internationalen Handel fördern, da transnationales Arbeiten verfügbarer und effizienter wird. Es muss demnach untersucht werden, welche Auswirkungen die Plattformarbeit für das Recht auf internationaler Ebene hat. Im internationalen Recht kann festgelegt werden, welche nationalen Gesetze von den Vertragsparteien anzuwenden sind. Der Schutz von Angestellten durch das Recht der sozialen Sicherheit hat demzufolge mit den privatrechtlichen Vereinbarungen zwischen Dienstleistungsanbietern und Dienstleistungsempfängern zu tun. Doch es gibt zahlreiche Lücken in den Sozialschutzvorkehrungen von Dienstleistungsanbietern. In vielen Ländern ist das Bewusstsein gewachsen, dass es Defizite im Sozialschutz von Plattformarbeitnehmern gibt, und es werden Maßnahmen geprüft, um den sozialen Status von Plattformarbeitnehmern zu verbessern. Analysen haben gezeigt, dass es in der gemeinsamen Verantwortung der Dienstleistungsanbieter und Dienstleistungsempfänger liegt, die Sozialversicherungsdeckung unter derselben nationalen Gesetzgebung zu verwirklichen. Aus Sicht des internationalen Rechts jedoch zeigt sich, dass die internationalen Rechtsnormen den Reformen oft Einschränkungen aufzwingen. Существует два аспекта, по которым занятость на цифровых платформах идёт вразрез с традиционным законодательством в сфере социального обеспечения. Во‐первых, различие между зависимым и независимым трудом становится неопределённым и неясным, поскольку границы размываются. Это создаёт серьёзную проблему для законодательства о социальном обеспечении, поскольку критерии зависимого и независимого труда должны быть чётко обозначенными. Что касается определения зависимого или независимого труда, немецкое законодательство наглядно демонстрирует, что в определении статуса занятости произошёл сдвиг от внешних и объективных критериев к принятию договаривающимися сторонами решений, которые исполняются в соответствии не только с законодательством о социальном обеспечении, но и с частным правом. Во‐вторых, труд на цифровых платформах тесно переплетён с цифровыми коммуникациями, создавшими глобальную среду общения. Поэтому он может способствовать развитию международной торговли и упрощению доступа к транснациональному рынку труда. Соответственно, представляется необходимым изучить возможные последствия занятости на цифровых платформах в контексте международного права. Международное право делает возможным выбор правовых норм, которых будут придерживаться договаривающиеся стороны. Таким образом, защита работников законодательством о социальном обеспечении связана с соглашениями, заключаемыми на основе частного права между поставщиками и получателями услуг. Пробелы в социальной защите поставщиков услуг носят широко распространённый характер. Во многих странах стала очевидной недостаточность социальной защиты работников цифровых платформ, и предметом пристального внимания стали меры, направленные на улучшение их социального статуса. Как показывает анализ, поставщик и получатель услуг несут совместную ответственность за то, чтобы социальн